Antibiotic G-418, a New Micromonospora-Produced Aminoglycoside with Activity Against Protozoa and Helminths: Antiparasitic Activity - Loebenberg, David (1975)
Antibiotic G-418 was shown to be superior to paromomycin and metronidazole in cecal amoebiasis. Of particular interest was the high degree of activity seen with a relatively short treatment at low levels. Although the antibiotic was trichomonacidal in vitro at low levels, in vivo results indicated that at levels tested the antibiotic did not always affect cures. The antibiotic appears to have promise as an anticestode agent, being more active than paromomycin against Hymenolepis nana and active as a single oral dose at low levels against Taenia spp.